Study on the Composite Driving System of Dexterous Hand - Luo Tianhong; Liu Lang; Chen Cai (Jixie chuandong)
Aiming at the problems which perform in the traditional driving mode,for example,the complex structure of motor drive system,the large volume of hydraulic drive system,the difficult control of air pressure drive system,a composite driving system actuated by micro- motor and shape memory alloy（ SMA） spring is proposed,then this system is applied to a humanoid multi- finger dexterous hand,the overall structure of the dexterous hand is simplified,and the control strategy gets optimized. The relation of the restoring force and displacement of the SMA spring is researched,then the relationships among knuckles movement and the influence factor on the contact force of grasping object are analyzed,by using the sliding mode PID intelligent control strategy,the movement of the finger is controlled,the control efficiency of dexterous hand is improved. Through the simulation of the dexterous hand model,the rationality and feasibility of the movement is verified,the basis for further study of composite driving system is provided.